The Influence of Water-Level Fluctuation on the Instability and Seepage Failure of Dump-Fill Cofferdam. (12th April 2022) - Hu, Yunqing; Huang, Jianyu; Tao, Zhipeng; Zhu, Junhua; Lv, Qing; Qiao, Jianwei; Cai, Weibin
Abstract : Due to the double disturbance effect of dredging and filling, there will be a problem with weir slope stability after the formation of a fill type saturated clay weir. In order to study the influence of water-level fluctuation on the instability and seepage failure of the dump-fill cofferdam, the saturated-unsaturated seepage theory and strength reduction method are embedded into the finite element system such that the fluid-solid coupling stability of the dump-fill cofferdam is analyzed. The results show that the influence of water-level fluctuation on the instability and seepage failure of the dump-fill cofferdam can be revealed by the coupling analysis excellently. The variation of the saturation line of the cofferdam is consistent with the variation of water-level rising, but the change response of the saturation line of the cofferdam has a lag property during the water-level decline process in that the water level changes faster. The maximum displacement of the cofferdam can be approximated as two stages, namely, the stable growth stage and the accelerated growth stage (slip initiation), in which the influence of the water-level fluctuation on the displacement of stable growth stage is more obvious. Based on the fluid-solid coupling analysis, the most dangerous sliding surface of the cofferdam is located at the position of the horse path, with a critical strength reduction coefficient of approximately 1.475. The possibility of seepage failure of the cofferdam will be increased if the water level exceeds the height of the impermeable wall.